Enhancement of heat transfer by nanofluids and orientations of the equilateral triangular obstacle. (June 2015) - Bovand, M.; Rashidi, S.; Esfahani, J.A.
Highlights: The heat transfer is improved by nanofluids and orientations of the obstacle. The role of solid volume fraction on the fluid flow and heat transfer is studied. There is an upward drift in the vortices for the diagonal facing flow. The maximum value of the average Nusselt number is for the vertex facing flow. Abstract: This paper simulates the forced convective heat transfer of Al2 O3 –water nanofluid over an equilateral triangular obstacle. Computations are performed for different orientations of the triangular obstacle (side, vertex and diagonal facing flows). The ranges of Reynolds number ( Re ) and solid volume fractions of nanoparticles ( φ ) are 1 ⩽ Re ⩽ 200 and 0 ⩽ φ ⩽ 0.05, respectively. Two-dimensional unsteady conservation laws of mass, momentum, and energy equations have been solved using finite volume method. The effects of Reynolds number, solid volume fractions of nanoparticles and different orientations of the triangular obstacle on the flow and heat transfer characteristics are investigated in detail. Detailed results are presented for wake length, streamline, vorticity, temperature contours and time averaged Nusselt number. Finally, the value of time averaged Nusselt number has been investigated in three equations using least square method which the effects of solid volume fraction of nanoparticles and Reynolds numbers are taken into account. The calculated results revealed that the maximum effect of nanoparticles on heat transfer rate augmentation is for the side facing flow and the minimum is related to the vertex facing flow. Also, the required Reynolds numbers for wake formation decrease with increase in solid volume fraction.